2017
DOI: 10.1016/j.vaccine.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Association of influenza vaccination during pregnancy with birth outcomes in Nicaragua

Abstract: Background: Studies have shown that influenza vaccination during pregnancy reduces the risk of influenza disease in pregnant women and their offspring. Some have proposed that maternal vaccination may also have beneficial effects on birth outcomes. In 2014, we conducted an observational study to test this hypothesis using data from two large hospitals in Managua, Nicaragua.Methods: We conducted a retrospective cohort study to evaluate associations between influenza vaccination and birth outcomes. We carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…An observational study in Australia found a 33% reduction in hospitalizations for respiratory illness among newborns of women vaccinated in the third trimester of pregnancy but no effect if vaccinated earlier in pregnancy [ 16 ]. An observational study in Nicaragua found reductions in preterm birth if vaccinated in the second and third trimesters of 13% and 34%, respectively, and a 20% and 36% reduction in LBW in infants of women vaccinated in the second and third trimester, respectively [ 17 ]. A retrospective analysis of 7 Vaccine Safety Datalink sites in the United States did not find any association between vaccine exposure and preterm and SGA overall, nor by trimester [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study in Australia found a 33% reduction in hospitalizations for respiratory illness among newborns of women vaccinated in the third trimester of pregnancy but no effect if vaccinated earlier in pregnancy [ 16 ]. An observational study in Nicaragua found reductions in preterm birth if vaccinated in the second and third trimesters of 13% and 34%, respectively, and a 20% and 36% reduction in LBW in infants of women vaccinated in the second and third trimester, respectively [ 17 ]. A retrospective analysis of 7 Vaccine Safety Datalink sites in the United States did not find any association between vaccine exposure and preterm and SGA overall, nor by trimester [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that there were differences in the implementation of the recommendation of influenza vaccination among pregnant women based on HROC status [3]. Hypothesizing that 61% of pregnant women with HROC and 53% without HROC would receive influenza vaccination, and assuming that 57% of pregnant women in our study population would have HROC [3], we calculated a sample size of 1274 women using a formula to detect differences between proportions. Likewise, hypothesizing that 61% of pregnant women with HROC and 53% without HROC would receive influenza vaccination recommendation from a healthcare provider, we calculated a sample size of 600 healthcare providers.…”
Section: Methodsmentioning
confidence: 99%
“…The study noted that vaccinated pregnant women had more chronic diseases compared to unvaccinated ones (60% vs 53%, p < 0.01), suggesting that, in spite of the recent recommendation to vaccinate all pregnant women regardless of risk status, health workers continued to prioritize women with HROC [3]. In order to determine if healthcare providers were recommending influenza vaccination to all pregnant women regardless of HROC status, we conducted a follow-up survey of knowledge, attitudes and practices of health personnel and pregnant women in Managua.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have further evaluated whether maternal influenza vaccination was associated with birth outcomes, including preterm birth and babies born small‐for‐gestational age (SGA). Though findings have been mixed, with some suggesting maternal vaccination reduced the risk of preterm delivery or was associated with SGA, while others have found no association . Influenza vaccination could, theoretically, prevent adverse birth outcomes by preventing potentially harmful inflammatory responses related to influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Though findings have been mixed, with some suggesting maternal vaccination reduced the risk of preterm delivery or was associated with SGA, while others have found no association. [4][5][6][7][8][9][10][11][12] Influenza vaccination could, theoretically, prevent adverse birth outcomes by preventing potentially harmful inflammatory responses related to influenza virus infection. Though rarely seen in vaccine safety surveillance, detrimental effects of influenza vaccination, such as increased risk of miscarriage, preterm birth, or babies born small-for-gestational age, have also been investigated.…”
Section: Introductionmentioning
confidence: 99%